The Effect of Institutional Management Quality Improvement of Livestock Group on The Welfare of People's Farmers - Fathurohman, Ferdi (Publikasi Indonesia, 2023)
Farmers in Subang Regency, West Java Province, are still focused on conventional farming and have not used group management. So that the level of welfare of farmers in Subang Regency is still not optimal. This study aims to look at the institutional management problems of smallholder livestock herds, increase the knowledge and skills of smallholder breeders in institutional procedures and livestock management and see the effect of increasing the quality of institutional management on the welfare of smallholder breeders. The method used in this research is FGD, counseling and coaching related to institutional and governance procedures, monitoring and evaluation by giving questionnaires to farmers through interviews and descriptive analysis. The results of this study, first, the problem of farmers is the low management of group institutions, especially regarding administration, feed and sales, breeders can understand and practice the procedures and institutional governance of beef cattle groups as an effort to increase additional income for the value of the cattle themselves, improve the quality of management groups have a significant effect on increasing group welfare. The conclusion of this study is that the problems that exist in smallholder farmer groups are the institutional problems of the livestock group that are not good including administrative management, storage and marketing. The training and assistance provided to farmers is able to understand and practice the procedures and governance of institutional management of beef cattle. Improving the quality of group institutional management has a positive and significant effect on improving the welfare of smallholder breeders.